Development and validation of a homogeneous mobility shift assay for the measurement of infliximab and antibodies-to-infliximab levels in patient serum - Wang, Shui-Long; Ohrmund, Linda; Hauenstein, Scott; Salbato, Jared; Reddy, Rukmini; Monk, Patrick; Lockton, Steven; Ling, Nicholas; Singh, Sharat (Journal of immunological methods, 2012)
Antibody-based drugs such as infliximab (IFX) are effective for the treatment of inflammatory bowel disease (IBD) and other immune-mediated disorders. The development of antibodies against these drugs may result in unfavorable consequences, including the loss of drug efficacy, hypersensitivity reactions, and other adverse events. Therefore, accurate monitoring of serum drug and anti-drug antibody levels should be an important part of therapy for patients being treated with an antibody-based drug. Current methods for the assessment of anti-drug antibodies and drug levels, involving various bridging ELISA and radioimmunoassay techniques, are limited by their sensitivity, interference, and/or complexity. To overcome these limitations, we have developed a non-radiolabeled homogeneous mobility shift assay (HMSA) to measure the antibodies-to-infliximab (ATI) and IFX levels in serum samples. Full method validation was performed on both the ATI- and IFX-HMSA, and the clinical sample test results were also compared with those obtained from a bridging ELISA method to evaluate the difference in performance between the two assays. Validation of the ATI-HMSA revealed a lower limit of quantitation of 0.012μg/mL in serum. The linear range of quantitation was 0.029–0.54μg/mL. The intra- and inter-assay precision was less than 20% of coefficient of variation (CV), and the accuracy (% error) of the assay was less than 20%. In serum samples, ATI as low as 0.036μg/mL can be measured, even in the presence of 60μg/mL of IFX in the serum. Sera from 100 healthy subjects were tested to determine the cut point of the assay. ATI-positive samples that had been previously analyzed by using a bridging ELISA from 100 patients were also measured by the new method. There was a high correlation between the two methods for ATI levels (p<0.001). Significantly, the new method identified five false-positive samples from the bridging ELISA method. Validation of the mobility shift IFX assay also showed high assay sensitivity, precision and accuracy. The HMSA method may also be applied to other protein-based drugs to accurately detect serum drug and anti-drug antibody levels.